ANALISIS UNDER VOLTAGE RELAY GENERATOR UNIT 1 PLTA SAGULING - Nugraha, A W; Y Mulyadia (Jurnal Permadi : Perancangan, Manufaktur, Material dan Energi, 2020)
Analysis of Under Voltage Relay Generator Unit 1 HEPP Saguling is a study to determine the efficiency of relay installation against voltage drops at HEPP Saguling. Under voltage relay works when there is a voltage difference between the primary and secondary PT within the range of the protective equipment. This research is a simulation using the ETAP 12.6 program. The data used are data obtained from the Generator Unit 1 system of the Saguling hydropower plant. This simulation is used to achieve the value of voltage drop, short circuit value, and delay trip under voltage relay. The lowest voltage drop in the 16.5 kV system is on bus 1 by 20% (3.3kV), the lowest voltage drop in the 500kV system is on bus 5 by 10.4% (52kV). Percentage difference in operating values ​​in the Internal Control System (ICS). namely 66 mA, 55 mA, and 76 mA Time to disturbances that occur in the connector between Generator unit 1 and CB 1 with a relay time delay of 96 ms and a CB trip of 396 ms.